Infographics a practical guide for librarians - Crane, Beverley E. (Practical guides for librarians, 2016)
Infographics: A Practical Guide for Librarians is designed for librarians who work with all age levels from youngsters to seniors at all educational, reading and language backgrounds, who must fulfill responsibilities that run the gamut from instructing patrons on information literacy skills to using electronic tools to marketing the library to locating funding, It includes basics about infographics followed by practical applications important for librarians. Visual examples serve as instructional models and exercises reinforce learning.